Isolation of cellulose nanocrystal from oil palm biomass with different formic acid hydrolysis time / Ahmad Afiq Jumhuri - Jumhuri, Ahmad Afiq (Faculty of Applied Sciences, 2017)
Oil palm biomass is a renewable resource that can be manipulated for many applications. Nanocellulose which can be extracted from oil palm biomass is renewable and biodegradable with wide range of possible applications. Cellulose nanocrystal (CNC) was isolated using formic acid hydrolysis with different hydrolysis time from oil palm biomass in the forms of oil palm mesocarp (OPM) and oil palm empty fruit bunch (OPEFB). CNCs isolated from both type of biomass were characterized using Fourier transform infrared (FTIR), X-Ray diffraction (XRD) and field emission scanning electron microscope (FESEM). Percentage yield of cellulose nanocrystals from OPEFB and OPM were around the same range of 28 -41 % showing the effect of hydrolysis time. FTIR analysis show peaks of lignin and hemicellulose at peaks l 200cm-1 and l 700cm-1 were completely removed after pretreatment process. XRD spectrum show the difference in crystal properties of the isolated CNC. CNC isolated from OPEFB show higher crystallinity index (60%) compared to that of OPM (55%). The morphology studies using FESEM show that CNC isolated from OPEFB to be globular while CNC from OPM show needle-like structure. Nanocellullose in the form of CNCs were successfully isolated from the study.